2014
DOI: 10.1371/journal.pone.0107146
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Role for CD248 (Endosialin) in PDGF-Mediated Skeletal Muscle Angiogenesis

Abstract: CD248 (Endosialin) is a type 1 membrane protein involved in developmental and pathological angiogenesis through its expression on pericytes and regulation of PDGFRβ signalling. Here we explore the function of CD248 in skeletal muscle angiogenesis. Two distinct forms of capillary growth (splitting and sprouting) can be induced separately by increasing microcirculatory shear stress (chronic vasodilator treatment) or by inducing functional overload (extirpation of a synergistic muscle). We show that CD248 is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…In most cases, perivascular staining was moderate to strong which is also in agreement with previous studies [19, 20]. Similar to the other tissue types examined, normal skeletal muscle demonstrated variable moderate staining of endothelial cells and strong perivascular cell staining, a finding that is consistent with those of Naylor, et al [29]. …”
Section: Resultssupporting
confidence: 91%
“…In most cases, perivascular staining was moderate to strong which is also in agreement with previous studies [19, 20]. Similar to the other tissue types examined, normal skeletal muscle demonstrated variable moderate staining of endothelial cells and strong perivascular cell staining, a finding that is consistent with those of Naylor, et al [29]. …”
Section: Resultssupporting
confidence: 91%
“…28 We found that mice with SMC-specific Cxcr4 deficiency showed an increased aortic expression of vimentin, a synthetic marker induced by PDGF-BB 29 , and of CD248 (endosialin), which is involved in PDGF-mediated cellular effects and associated with a synthetic SMC phenotype (Figure 5G, Supplemental Figure 5R,S). 30,31 Moreover, staining for vimentin, CD248, CD68 and lipids (Nile red) revealed a higher prevalence of de-differentiated SMCs in plaque caps of these mice (Figure 5H). In vitro , both WNT3a and CXCL12 increased the expression of contractile markers ( Tagln, smoothelin, CNN1 ) in cultured hAoSMCs, whereas the expression of synthetic markers was reduced (for CD248 after WNT3A treatment, Figure 5I, Supplemental Figure 5T) or not altered (after CXCL12 treatment, Figure 5J, Supplemental Figure 5U), respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Endosialin-deficient mice are, unless pathologically challenged, phenotypically normal (27), although they display some delay of developmental vascular remodeling caused by perturbed pericyte function (28,29). Earlier studies have reported no overt difference in the growth of subcutaneous tumors in wild-type and endosialin-deficient mice (27,28,30).…”
Section: Introductionmentioning
confidence: 99%